2019
DOI: 10.1002/ccr3.2062
|View full text |Cite
|
Sign up to set email alerts
|

Mature cystic teratoma of ovary with squamous cell carcinoma arising from it

Abstract: Key Clinical Message Clinicians, pathologists, and radiologists should be aware of rare malignant ovarian tumors arising in mature cystic teratoma (MCT). Suspicion should be raised if the patient is elderly, the tumor is huge, and the tumor has large solid foci. However, malignant transformations in MCTs in younger women have been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…In our present case also, some thickened or solid parts in the cyst wall were identified on gross examination of surgical pathology specimen. Other studies like those done by Bashyal R et al [3] , by Gupta N et al [4] , by Gupta V et al [10] , by Santwani PM et al [6] and by Maharjan S [15] also show similar findings in gross examination of the tumor specimen itself. Finally, we can say that the teratomas with larger size & variable cyst-wall thickness with thickened or solid area (parts) grossly visible in the cyst-wall have maximum chance of malignant transformations.…”
Section: Table 3: Comparative Evaluation Of Tumor Size Of Different Ssupporting
confidence: 72%
See 3 more Smart Citations
“…In our present case also, some thickened or solid parts in the cyst wall were identified on gross examination of surgical pathology specimen. Other studies like those done by Bashyal R et al [3] , by Gupta N et al [4] , by Gupta V et al [10] , by Santwani PM et al [6] and by Maharjan S [15] also show similar findings in gross examination of the tumor specimen itself. Finally, we can say that the teratomas with larger size & variable cyst-wall thickness with thickened or solid area (parts) grossly visible in the cyst-wall have maximum chance of malignant transformations.…”
Section: Table 3: Comparative Evaluation Of Tumor Size Of Different Ssupporting
confidence: 72%
“…In our present study, it is 12.58 U/ml. In other similar studies done by Bashyal R et al [3], by Goudeli C et al [7] , by Suna Avc1 et al [9] and by Maharjan S [15] , they are 24.19 U/ml, 37.50 U/ml, 57.00 U/ml and 10.70 U/ml respectively. Gupta V et al [10] also reported two cases of malignant transformations in ovarian teratoma with serum CA 125 levels of 40 U/ml & 50 U/ml respectively.…”
Section: Table 3: Comparative Evaluation Of Tumor Size Of Different Smentioning
confidence: 52%
See 2 more Smart Citations
“…Mature cystic teratomas are the germ cell tumor deriving from primordial germ cells and composes of tissues arising from endoderm, mesoderm, and ectoderm in terms of histology [1]. Malignant elements or the secondary benign tumors in MCTs can also be seen [1,2]. However, the incidence of their co-exist in MCTs is extremely rare.…”
Section: Introductionmentioning
confidence: 99%